Heterogenic nature of guerrilla gardening - Agnieszka Gralinska-Toborek (Journal of Aesthetics & Culture)
For some time now, researchers from various academic disciplines have been engaged in the study of green guerrilla gardening, a grassroots activity involving the planting of vegetation in public spaces. In essence, they view it as a social movement with the objective of reclaiming control of public space and modifying its functionality. However, Author identifies a greater diversity within this movement, which he categorises into four basic types of activity: gardening, activism, art and farming. Each of these categories can be further subdivided into distinct areas of focus, including the beautification of urban spaces, the promotion of social change, the provision of food sources, the advancement of education, and the fostering of community building. The diverse nature of guerrilla gardening allows it to fulfil a multitude of roles and objectives. It can therefore be concluded that the phenomenon is heterogeneous, and that the term used to describe it should be understood more broadly in order to encompass this range of activities. Empirical research is increasingly indicating a discrepancy between the practice of gardeners and the expectations of theorists. For example, the use of military terminology, while humorous, can be seen as an overly optimistic expectation of the actions of these often humble gardeners, while emphasising an activist (political) stance. Furthermore, the author notes that research on guerrilla gardening lacks in-depth aesthetic reflection.